A Generic Strategy to Create Mechanically Interlocked Nanocomposite/Hydrogel Hybrid Electrodes for Epidermal Electronics - Wang, Qian; Li, Yanyan; Lin, Yong; Sun, Yuping; Bai, Chong; Guo, Haorun; Fang, Ting; Hu, Gaohua; Lu, Yanqing; Kong, Desheng (Nano-Micro Letters, 2024)
Stretchable electronics are crucial enablers for next-generation wearables intimately integrated into the human body. As the primary compliant conductors used in these devices, metallic nanostructure/elastomer composites often struggle to form conformal contact with the textured skin. Hybrid electrodes have been consequently developed based on conductive nanocomposite and soft hydrogels to establish seamless skin-device interfaces. However, chemical modifications are typically needed for reliable bonding, which can alter their original properties. To overcome this limitation, this study presents a facile fabrication approach for mechanically interlocked nanocomposite/hydrogel hybrid electrodes. In this physical process, soft microfoams are thermally laminated on silver nanowire nanocomposites as a porous interface, which forms an interpenetrating network with the hydrogel. The microfoam-enabled bonding strategy is generally compatible with various polymers. The resulting interlocked hybrids have a 28-fold improved interfacial toughness compared to directly stacked hybrids. These electrodes achieve firm attachment to the skin and low contact impedance using tissue-adhesive hydrogels. They have been successfully integrated into an epidermal sleeve to distinguish hand gestures by sensing muscle contractions. Interlocked nanocomposite/hydrogel hybrids reported here offer a promising platform to combine the benefits of both materials for epidermal devices and systems. Highlights: 1 Nanocomposite/hydrogel hybrid electrodes are created with high interfacial toughness by introducing soft microfoams as the mechanically interlocking layer. 2 In the hybrid electrodes, silver nanowires and hydrogels are electrically connected through the porous microfoams, achieving high conductivity and low contact impedance for high-quality biopotential recordings. 3 The microfoam-enabled bonding strategy is generally applicable to diverse polymer substrates.